An Empirical Model of Acceptance of Mobile Payment in Malaysia (Global Journal of Management and Business Research, 2022)
Mobile payment refers to a payment method by which a consumer pays a bill for goods or services through a mobile terminal. mobile payment users can send payment instructions directly or indirectly to a bank via mobile devices, thereby enabling currency payments and funds transfers. It realizes the integration of terminal equipment, Internet, application providers and financial institutions, and completes financial business such as currency payment. However, the adoption rates of this payment method is relative low in Malaysia. This research aims to identify and explore key factors that affect the decision of whether to use mobile payments. Four well-established theories, Theory of Rational Action(TRA), Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology(UTAUT), Compass Acceptance Model for the analysis and evaluation of mobile service(CAM) are applied to investigate user acceptance of mobile payments. A empirical model for acceptance of mobile payment in Malaysia is established in this paper. Survey data from mobile payments users will be used to test the proposed hypothesis and the model. The result of data analysis shows that Malaysian consumers#x2019; perceptions of cost has no statistically significant relationship with attitude to adopt mobile payment. On the other hand, the factor of Consumer Trust plays the most important role, followed by Perceived Usefulness, Perceived Ease of Use, and Subjective Norm.
Keywords: malaysia; acceptance; mobile payment; consumer trust; perceived usefulness; perceived ease of use; subjective norm; perceived cost